2013
DOI: 10.1371/journal.pone.0074775
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glutathione-S-Transferases (GST) Polymorphisms and Hypermethylation of Relevant Genes on Risk of Prostate Cancer Biochemical Recurrence: A Meta-Analysis

Abstract: IntroductionAccurate prediction of the biochemical recurrence (BCR) is critical for patients after intended curative therapy like radical prostatectomy (RP) or definitive radiotherapy for prostate cancer. Glutathione-S-transferases polymorphisms as well as hypermethylation of GSTP1 and functional genes in carcinogenesis, including tumor suppression gene (APC), hormone receptor that regulates cell growth and differentiation gene (RARbeta) were reported to be associated with BCR. Nevertheless, the reported resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…A recent meta-analysis based on 4 case-control studies and 7 cohort studies including 12 data sets and 3.037 PCa patients confirms the relation between PSA failure and Glutathione-S-transferases ( GSTM1 and GSTP1 ) polymorphisms and hypermethylation of GSTP1 and APC [27]. However, use of single gene hypermethylation for prediction of prognosis in PCa may produce unspecific results since it may also be present in other neoplasms and non-malignant tissues [9].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis based on 4 case-control studies and 7 cohort studies including 12 data sets and 3.037 PCa patients confirms the relation between PSA failure and Glutathione-S-transferases ( GSTM1 and GSTP1 ) polymorphisms and hypermethylation of GSTP1 and APC [27]. However, use of single gene hypermethylation for prediction of prognosis in PCa may produce unspecific results since it may also be present in other neoplasms and non-malignant tissues [9].…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic stage, Gleason score, and surgical margin status are independent predictors of biochemical recurrence and are used in nomograms to predict outcome (10). A recent meta-analysis has shown that GSTP1 hypermethylation may also be a potential predictive biomarker (11).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced reduce representation bisulfite sequencing (ERRBS) can detect genome-wide DNA methylation at single-base resolution including CGI shores and allele-specific methylation (ASM) at various regions (Lin et al 2013). Based on the ChIP-Seq, Chen et al, 2013 showed that ERG restores an androgen receptor (AR) transcriptome in PTEN-deleted PCa. In addition, methylated DNA immunoprecipitation sequencing (MeDIP-Seq) method involves isolation of methylated fragments of the genome by using an antibody (Thu et al 2009).…”
Section: Identifying Pca Mutations Using Next Generation Sequencing Mmentioning
confidence: 99%
“…CpG island hypermethylation of glutathione-S-transferase P (GSTP1) promoter DNA, resulting in the loss of GSTP1 expression (Lin et al 2001). A number of methylation profiles have been developed and are being evaluated as potential markers for early diagnosis and risk assessment (Chen et al 2013). In the recent-past, iCLIP-Seq methods to infer RNA-Protein interactions at a higher resolution is made available (Huppertz et al 2014).…”
Section: Identifying Pca Mutations Using Next Generation Sequencing Mmentioning
confidence: 99%